RESEPSI MAHASISWA ILMU KOMUNIKASI UNIVERSITAS RIAU PADA ISU PENYIMPANGAN SEKSUAL LEWAT VIDEO MUSIK “TO GOOD AT GOODBYES” KARYA SAM SMITH - Siprianus Lucky Samosir Ph; Ikhma Zurani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The music video for "Too Good At Goodbyes" which had become the center of attention of music lovers because of Sam Smith's courage to reveal to the public his change of sexual orientation, through this song Sam Smith also told that he created this song to tell the public the love story he experienced was really enough made him sad and from this song he poured out all his sadness and revealed that he was a gay lover. The song, which has quite a lot of listeners, has become a byword among music connoisseurs because the song has a sad ballad theme and this song went viral in 2017 because the singer revealed her heartbreak through this song This research is a type of descriptive qualitative research with a constructivism paradigm that focuses on the analysis of Stuart Hall's reception that focuses on encoding and decoding using purposive techniques to determine informants. The data were obtained through a process of observation, in-depth interviews and documentation with nine informants. The data analysis technique used is reception analysis consisting of data collection, interpretation and reception. While the technique of checking the validity of the data using triangulation. The results of the first study were that all informants positively accepted and agreed with what was conveyed (dominantly) in the “Too Good At Goodbyes” Music Video with different backgrounds, five of the seven informants were victims who experienced acts of sexual deviance. The second is that some informants have the meaning of accepting or agreeing with the messages given in the “Too Good At Goodbyes” Music Video but giving exceptions (negotiated) and rejecting (oppositional) messages from several messages of Sexual Deviance in the “Too Good At Goodbyes” Music Video based on references they have such as the Music Video "Too Good At Goodbyes" have not been able to prevent acts of sexual deviance and illogical actions from the character's environment. Differences in how informants perceive sexual deviance in the “Too Good At Goodbyes” Music Video are caused by several factors, namely age, education, experience and culture. Keyword : Reception, Sexual Deviance, Music Video